BASKETBALL SHOOTING FUNDAMENTALS: AN IN-DEPTH BIOMECHANICAL ANALYSIS - Cabarkapa, Dimitrije (Sport- és Egészségtudományi füzetek, 2025)
In the game of basketball, shooting efficiency has a large impact on securing the winning game outcome. However, despite its importance, there is a notable gap in the sci-entific literature focused on examining the biomechanical characteristics of proficient shooters. Thus, a series of re-cently published research reports by Cabarkapa et al. have attempted to address this issue and compare the shooting mechanics between non-proficient and proficient basket-ball shooters.